Pembiasaan Mukhadharah untuk Membina Potensi dan Ahlakul Karimah Siswa di MTs Ma’arif Kaligowong - Musafa, Samsul; Irodati, Fibriyan (IAINU Kebumen, 2025)
This study examines the habituation of mukhadharah as a means of developing students’ potential and noble character at MTs Ma’arif Kaligowong. The purpose of this research is to: (1) identify the process of implementing character and potential development through mukhadharah, (2) determine the outcomes of this habituation, and (3) explore supporting and inhibiting factors. This research employs a qualitative field study design with data collected from the head of the madrasah, mukhadharah coaches, teachers, and students through observation, interviews, documentation, and triangulation, followed by data reduction, display, conclusion drawing, and verification. The findings reveal that mukhadharah effectively fosters students’ self-confidence, public speaking skills, discipline, and noble character. Supporting factors include institutional encouragement, teacher participation, and student motivation, while inhibiting factors consist of students’ lack of confidence and uneven teacher involvement. Mentoring and activity variation helped overcome these barriers. In conclusion, mukhadharah serves as an essential strategy for the sustainable development of students’ religious and social character